REVEGETATION IN SOLAR PHOTOVOLTAIC FARMS IN MEDITERRANEAN AREAS (FRESENIUS ENVIRONMENTAL BULLETIN, 2013)
In order to ascertain the native species best adapted to different soil and climatic conditions in Mediterranean areas degraded by the installation of solar photovoltaic farms, six shrub species, which would act as a hedge, were planted around the perimeter of a photovoltaic farm (Olea europaea var. sylvestris, Pistacia lentiscus, Pistacia terebinthus, Quercus coccifera, Quercus ilex and Retama sphaerocarpa). In the midst of the solar panels, eight species for revegetation, acting as a cover to protect the soil, were also planted (Cistus ladanifer, Cistus monspeliensis, Lavandula angustifolia, Lavandula stoechas, Phillyrea angustifolia, Rosmarinus officinalis, Romarinus officinalis var. postratus and Thymus vulgaris) under conditions of sun or shade (shaded by solar panels). During 2009 and 2010 the plants of each species were checked and their survival and growth were recorded. In the hedge, Retama sphaerocarpa (100%), Olea europaea var. sylvestris (95.8%) and Pistacia lentiscus (95.8%) had the highest survival percentages. These were also the species that presented the highest apical growth after two years (18.3 +/- 14.7, 12.3 +/- 12.4 and 12.1 +/- 5.1 cm, respectively). Only two of the species planted under the solar panels had a survival percentage above 50% and these were Cistus monspeliensis (62.5%) and Phillyrea angustifolia (97.9%), with increases of the apical growth by 25.6 +/- 9.9 cm and 10.3 +/- 9.8 cm, respectively. The development of plants under either sun or shade was not a statistically significant factor. The results can be extrapolated to other Mediterranean areas dealing with the same problems.